The Workload of a College English Teacher A Statement of Policy. - National Council of Teachers of English, Champaign, IL.; National Council of Teachers of English, Champaign, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
The official position on the workload of college teachers of English adopted by the National Council of Teachers of English (NCTE) discusses factors bearing upon the determination of a reasonable teaching schedule. Evaluation of student composition, grading fatigue, class size, conference hours, research, committees, clubs, lectures, and class visitations are commented on. The adoption of the suggested NCTE standards is urged. (RL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Courses; Curriculum; English Curriculum; Student Teacher Ratio; Teaching Assignment; College English; College Faculty; Colleges; English Departments; Teachers; Teaching Load